Concept and its implementation during the reconstruction of the church of blessed virgin Mary in Chojna = Koncepcja i jej realizacja w trakcie odbudowy kościoła pw. NMP w Chojnie - Płotkowiak, Maciej (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
St. Mary's parish church in Chojna was erected at the turn of XIV and XVc. in a shape of three aisles, hall church without transept, completed from the west with a single tower and from the east with polygonal presbytery with an ambulatory attached. The convergence of characteristic structural and decorative features with employed ones in medieval churches being attributed to Hinrich Brunsberg's fabric resulted in such a way, that also authorship of St. Mary in Chojna was assigned to this legendary architect and master builder of late Middle Ages period.
Keywords: Chojna; kościół farny; odbudowa kościoła; Brunsberg; St. Mary's parish church; reconstruction